Znaczenie poczucia wstydu w wychowaniu - Zajdel, Krzysztof (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article deals with a sense of shame, which occurs quite often in schools. This feeling is not foreign students, but also teachers, although they are due to experience and age, can itself probably manage it, as opposed to students. His thoughts increased with a small probe among teachers who see the problem, but few do it in their pedagogical activity. Shame is known and tested by educators, psychologists, medicine, but this translates into a potential training of teachers in this area. Quite often it serves as a tool to influence the affairs of education.
Keywords: be ashamed; school; shame; upbringing